STUDENTS’ ABILITY AND PROBLEMS IN WRITING REVIEW TEXT AT GRADE XII SMAN 4 KERINCI - Anamaryanti Anamaryanti; Hermawati Syarif; Yenni Rozimela (Fakultas Bahasa dan Seni UNP, 2015)
KEMAMPUAN DAN MASALAH SISWA DALAM MENULIS TEKS REVIEW DI KELAS XII SMAN 4 KERINCIAbstractThis article is written to describe research about students' ability in writing text review, problems faced by students in writing text review and cause of the problem tersebut. Data of this research is the result of students’ writing and the result of interview with the students. The result of this descriptive research shows that students’ ability in writing reviews is good enough. Although the average grade of students is categorized sufficiently, students also faced problems in writing reviews text. Their problems relate to vocabulary, grammar, general structure, organizing ideas, and spelling and punctuation. The findings also show that the cause of the problem is the first language interference, the target language is so difficult, and the lack of knowledge of students about the components in writing text reviews.Key words: writing ability, writing problems, review text Abstrak Artikel ini ditulis untuk mendeskripsikan penelitian tentang kemampuan siswa dalam menulis review text, masalah-masalah yang dihadapi siswa dalam menulis review text dan penyebab masalah tersebut. Data penelitian ini adalah hasil tulisan siswa dan hasil wawancara dengan siswa. Hasil penelitian deskriptif ini menunjukkan bahwa kemampuan siswa dalam menulis review cukup. Meskipun nilai rata-rata siswa dikategorikan cukup, siswa juga menemukan masalah dalam menulis review text. Masalah-masalah mereka berhubungan dengan kosa kata, tata bahasa, struktur umum, mengorganisasikan ide dan ejaan serta tanda baca. Temuan juga menunjukkan bahwa penyebab masalah tersebut adalah interferensi bahasa pertama, bahasa sasaran yang begitu sulit, dan kurangnya pengetahuan siswa tentang komponen dalam menulis review text.Kata Kunci: writing ability, writing problems, review text